Moonlight cycles synchronize oyster behaviour. (31st January 2019) - Payton, Laura; Tran, Damien
Abstract : Organisms possess endogenous clock mechanisms that are synchronized to external cues and orchestrate biological rhythms. Internal timing confers the advantage of being able to anticipate environmental cycles inherent in life on Earth and to prepare accordingly. Moonlight-entrained rhythms are poorly described, being much less investigated than circadian and circannual rhythms synchronized by sunlight. Yet focus on these lunar rhythms is highly relevant to understanding temporal organization of biological processes. Here, we investigate moonlight cycle effects on valve activity behaviour of the oyster Crassostrea gigas . Our results show that oysters modulate valve behaviour according to both intensity and direction of the lunar illumination cycle. As a consequence, valve opening amplitude is significantly increased at third quarter Moons (decreasing lunar illumination) compared with first quarter Moons (increasing lunar illumination) despite identical lunar illumination, and this indicates that oyster modulation of valve behaviour by moonlight cycles is not a direct response to lunar illumination. We propose that oysters use moonlight cycles to synchronize behaviour and also other physiological and ecological aspects of this benthic mollusc bivalve.